USER - skala do pomiaru wykorzystania wyników badań marketingowych w przedsiębiorstwie - Mącik, Radosław (USER - Scale for Measurement of Usage of Marketing Research Results in Enterprise, 2006)
Proper management of information becomes a crucial thing for enterprise success in intensely competitive business environment. Measuring information and knowledge usage - both generated from undertaken research is important in such circumstances. The paper presents methodology and usage possibilities of USER - reliable and valid multidimensional scale measuring the types and extent of knowledge utilization based on the usage of market research - proposed by A. Menon and J. В Wilcox. Advantages of this scale were a main reason for the author to begin translation into Polish and adaptation procedure. The article contains selected results of the initial preliminary study on small sample of Polish managers using early form of adapted scale. The author also compares some results from original samples used by Menon and Wilcox with results of his own preliminary tests. Main limitations of preliminary tests are considered, as well as full text of scale items (in Polish).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 528-534